The Timeliness of Publication of Periodic Reports in the Time of the COVID-19 Pandemic on the Example of Companies Listed on the Warsaw Stock Exchange - Lisicki, Bartłomiej; Franczak, Iwona (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2023)
Objective: The aim of the article is to assess the timeliness of the submission of periodic reports by issuers listed on the Warsaw Stock Exchange (WSE) during the COVID-19 pandemic (2020–2022) and to compare it with that of submissions in the years immediately preceding the pandemic (2018–2019). To this end, the following research hypothesis was formulated: the COVID-19 pandemic negatively influenced the timeliness of the publication of periodic reports by companies listed on the WSE, by extending the average time of their submission compared to previous years.Research Design & Methods: In terms of research methods, a literature review and analysis of legal acts were used in the theoretical part, while statistical verification was used to estimate the timeliness of the submission of periodic reports by companies from the Warsaw Stock Exchange.Findings: The research results did not bear out the research hypothesis. Detailed data on the median number of publication days of periodic reports preceding the deadline for submission of the report indicate that in as many as 11 of the 15 indicated subgroups the median number of publication days of periodic reports preceding the deadline is higher. This indicates that in 2020–2022 WSE issuers published reports earlier than they had in 2018–2019.Implications / Recommendations: The research results show that the COVID-19 pandemic did not adversely affect the timely publication of periodic reports of companies listed on the Warsaw Stock Exchange. This is because there was no significant extension of the time to make financial statements available in the years 2020–2022.Contribution: The research contributes to the knowledge of an important feature of financial statements: timeliness. The authors note the lack of research in this area during the COVID-19 pandemic, a period that saw dynamic changes in capital markets.